2020
DOI: 10.1002/brb3.1655
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin inhibits oxidative stress and antagonizes Alzheimer's disease by up‐regulating SIRT1

Abstract: Introduction Alzheimer's disease (AD) is a progressive neurodegenerative disease. It can lead to progressive cognitive impairment, memory loss, and behavioral alterations. So far, the exact cellular and molecular mechanisms underlying this disorder remain unclear. And there are no effective treatments to prevent, halt, or reverse AD. In recent years, Chinese traditional medicine has become a new force in the treatment of AD, and the typical representatives of natural herbal ingredients are curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Impaired mitochondrial morphology has been implicated in increased electron leak from the mitochondrial respiratory chain and loss of mitochondrial membrane potential, which is the initial stage of mitochondrial dysfunction [ 37 ]. Bisdemethoxycurcumin has been widely used to suppress the burst of ROS and counteract oxidant stress in various diseases [ 26 , 28 , 38 ]. In our study, increased ROS levels and decreased mitochondrial membrane potential induced by LPS were partially rectified by dietary bisdemethoxycurcumin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired mitochondrial morphology has been implicated in increased electron leak from the mitochondrial respiratory chain and loss of mitochondrial membrane potential, which is the initial stage of mitochondrial dysfunction [ 37 ]. Bisdemethoxycurcumin has been widely used to suppress the burst of ROS and counteract oxidant stress in various diseases [ 26 , 28 , 38 ]. In our study, increased ROS levels and decreased mitochondrial membrane potential induced by LPS were partially rectified by dietary bisdemethoxycurcumin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study con rmed the components of Curcumae Radix extract, such as curcumin, demethoxycurcumin, and bisdemethoxycurcumin [12]. Curcumin suppresses breast cancer [20], demethoxycurcumin has neuroprotective effects [21], and bis-demethoxycurcumin inhibits Alzheimer's disease by suppressing oxidative stress [22]. In neurodegenerative diseases involving mitochondrial dysfunction, demethoxycurcumin, which is a natural derivative of curcumin, exerts neuroprotective activity [21].…”
Section: Discussionmentioning
confidence: 95%
“…It is known that Aβ oligomers temporarily inhibit AMPK and cause metabolic dysfunction in hippocampal neurons in the early AD brain [83]. In addition, AMPK alleviates AD by activating sirtuin 1, whose expression is reduced with impairment of spatial learning and memory [84,85]. Previous studies have confirmed the association between integrin or AMPK and neurodegenerative disease, and our results showed changes in the integrin and AMPK pathways in insulin resistance-induced neuronal cells, suggesting the possibility that metabolic disease may induce AD.…”
Section: Discussionmentioning
confidence: 99%